Implicit bias to food and body cues in eating disorders: a systematic review - Paslakis, Georgios; Scholz-Hehn, Anne Deborah; Sommer, Laura Marie; Kühn, Simone (Eating and Weight Disorders-Studies on Anorexia Bulimia and Obesity, 2020)
Background: Rigid, restrictive eating patterns, fear of gaining weight, body image concerns, but also binge eating episodes with loss of control leading to overweight, at times followed by compensatory measures to control weight, are typical symptoms in eating disorders (EDs). The regulation of food intake in EDs may underlie explicit processes that require cognitive insight and conscious control or be steered by implicit mechanisms that are mostly automatic, rapid, and associated with affective—rather than cognitive—processing. While introspection is not capable of assessing implicit responses, so-called indirect experimental tasks can assess implicit responses underlying a specific behavior by-passing the participant’s consciousness. Here, we aimed to present the current evidence regarding studies on implicit biases to food and body cues in patients with EDs. Methods: We performed a systematic review (PRISMA guidelines). We included controlled studies performed in clinical ED cohorts (vs. healthy control subjects or another control condition, e.g., restrictive vs. binge/purge AN) and using at least one indirect assessment method of interest. Results: Out of 115 screened publications, we identified 29 studies fulfilling the eligibility criteria, and present a synthesis of the essential findings and future directions. Conclusion: In this emerging field of research, the present work provides cornerstones of evidence highlighting aspects of implicit regulation in eating disorders. Applying both direct (e.g., self-reports) and indirect measures for the assessment of both explicit and implicit responses is necessary for a comprehensive investigation of the interplay between these different regulatory mechanisms and eating behavior. Targeted training of implicit reactions is already in use and represents a useful future tool as an add-on to standard psychotherapeutic treatments in the battle against eating disorders. Evidence level: 1 (systematic review).
CRIS-Team Scopus Importer:2020-08-14
Keywords: Anorexia nervosa; Approach avoidance task; Bias; Binge eating disorder; Bulimia nervosa; Implicit